Artificial Intelligence and Christian Religious Education Management: Finding the Balance between Technology and Spirituality - Sihombing, Octavianus RM (Indonesian Journal of Advanced Research, 2024)
In digital era, Artificial Intelligence (AI) is pivotal in transforming various sectors, including education. This research explores balancing AI utilization in managing Christian Religious Education while preserving essential spiritual values. Using a qualitative method and literature review, the study analyzes recent scholarly resources on AI in education and its spiritual impact. The findings reveal AI's potential to improve the efficiency of Christian Religious Education management through administration, personalized learning, and data analysis. However, concerns exist about reduced human interaction and overlooked spiritual elements. A careful approach to AI integration is essential, emphasizing the preservation of spiritual values and local wisdom, ensuring AI serves as a supportive tool, not a replacement, in fostering holistic character development.